АРАБ ТИЛИ ҲАҚҚЫНДА УЛЫЎМА МАҒЛЫЎМАТ - Ишаев, Ж. (FAN va JAMIYAT, 2019)
There is given some interesting information about the Arabian language, possibilities to learn this language in our country, history of development the language and pecularities of this language.